Pembelajaran Tari Muli Siger Menggunakan Model Student Team Achievent Division (STAD) di SMA Negeri 13 Bandarlampung - Luh Puspita Gita Nurani; I Wayan Mustika; Riyan Hidayatullah (Jurnal Seni dan Pembelajaran, 2018)
STAD is the simplest cooperative learning model that is applied to deal with the students’ ability which is heterogeneous. The use of stad that was applied at SMAN 13 Bandarlampung was aimed to find out the process and the result of muli siger dance learning that was applied in group and based on constructivism theory. This research was qualitative descriptive research by observing the learning of muli siger dance directly. The data were collected by using observation, interview, and documentation. The data were analyzed by data reduction, data representation and data verification. The dance learning process was conducted in 3 steps that was teacher presentation, group division and team work with 10 students as respondents. The result of this research showed the students had master all of the movement varieties well and it can be concluded the implementation of the dance learning process at SMAN 13 Bandarlampung had administered optimally. STAD adalah model pembelajaran kooperatif yang paling sederhana yang diterapkan pada kemampuan siswa yang heterogen. Penggunaan STAD yang diterapkan pada sman 13 bandar lampung bertujuan untuk mengetahui proses dan hasil pembelajaran tari muli siger yang diterapkan dalam kelompok dan berdasarkan teori konstruktivisme. Penelitian ini merupakan deskriptif kualitatif dengan mengamati pembelajaran tari muli siger secara langsung. Data dikumpulkan dengan menggunakan observasi, wawancara, dan dokumentasi. Data dianalisis dengan reduksi data, representasi data dan verifikasi data. Proses pembelajaran tari muli siger dilakukan dalam 3 langkah yaitu presentasi guru, pembagian kelompok dan kerja tim dengan 10 siswa sebagai responden. Hasil penelitian menunjukkan bahwa pelaksanaan proses pembelajaran tari di SMAN 13 Bandar lampung telah dilaksanakan secara optimal.